Nitrogen Fertigation in Drip-Irrigated Cucumber Grown in Greenhouse - Pattanaaik, S.K.; Debnath, P.; Singh, Barun; Warade, S.D.; Pandey, A.K. (Indian Journal of Hill Farming, 2019)
A study was conducted in greenhouse to evaluate the response of fertigation in cucumber (Cucumis sativus L.). The cucumber plants were grown in beds made inside the green house. The experiment was laid out in randomised block design with comprising of four treatments and eight replications. The treatments were T1-5.8 mmol/lt N2, T2-11.8 mmol/lt N2, T3-17.8 mmol/lt N2 and T4-23.8 mmol/lt N2. The nutrient was applied through drip irrigation at calculated volume to each plant in each treatment. FYM @ 10tonnes per hectare was incorporated in the soil at the time of bed preparation. The total amount of water applied to each plant was 375.69 litres and the total number of fertigation given was 106 times during the entire period of investigation starting form planting (6th February, 2015) to final harvest of crop (12th May, 2015) maximum. Application of nitrogen through drip irrigation showed a positive effect on the fruit yield and number of fruits per plant. The treatment T3 (17.8 mmol/lt N2) produced highest yield and number of fruits which was significantly higher than the other treatments. The yield and number of fruits decreased with higher level of N2 application in treatment T4 (23.8 mmol/lt N2).